Integrated interface system for tool path generation of STEP file - Saiful Bahri, Mohamed; Mohd, Minhat; Tengku Mohd Shahrir, Tengku Sulaiman,; Mohd Shahir, Kasim; Ahmad Syafiq, Mohamed; Ahmad Ridzuan, Mohamed; Jailani, Ismail (2019)
STEP file is a CAD file , which is Standard for the Exchange of Product model data. It is the next generation of data model between CAD/CAM and CNC system . It contains three-dimensional (3D) data in ISO 10303-21 format that can be recognized and utilized by most of CNC programs. However, not all data available in the STEP files are suitable for CNC G-Code programming. This paper describes the design, development and testing of an Integrated Interface System , which aims to provide tool path generation for machining operation using STEP file as an input file . The system provides function of reading and extracting the relevant information associated with the machining data from STEP file , which eventually writes the Geometric Code (G-Code) file format as an output file . The sample of machined block is designed from 3D CAD modeler that consisted of features need to be machined from a blank work piece and saved in the STEP file format. The validation process uses the tool path simulation via PC based CNC controller .